1970
DOI: 10.2307/3053071
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Formal Sanctions as a Deterrent to Deviant Behavior

Abstract: The imposition of penalities for violation of criminal laws has been traditionally justified for such reasons as social justice and retribution. Today, perhaps the main justification for imposing severe penalties on those who violate the law is that such punishments serve as a specific deterrent to future violations by the offender and as a general deterrent to violations by others who might be tempted to follow his lead.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1975
1975
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…Likewise, another critical variable in Rational Choice theory is the seriousness of the offense which shapes the severity of the potential punishment, was not a significant variable in shaping the likelihood of walking while intoxicated all else equal. These results support the work of those who argue that there are no direct effects, regarding the perceived certainty and severity of sanctions, on deterring an individual's decision to deviate (Salem & Bowers, 1970).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Likewise, another critical variable in Rational Choice theory is the seriousness of the offense which shapes the severity of the potential punishment, was not a significant variable in shaping the likelihood of walking while intoxicated all else equal. These results support the work of those who argue that there are no direct effects, regarding the perceived certainty and severity of sanctions, on deterring an individual's decision to deviate (Salem & Bowers, 1970).…”
Section: Resultssupporting
confidence: 89%
“…In a study of college students, Salem and Bowers (1970) found that 'for both getting drunk and violating alcohol-use rules, the per interval effects within the disapproval contexts are very small' (p. 28). The certainty and severity of formal sanctions had no direct effect on deterring the individual.…”
Section: Formal Sanctionsmentioning
confidence: 95%
“…The results presented here suggest deterrence does not seem to be operating. This conforms to research into the effects of legitimacy on minor rule violations (Tyler, 1990; see also Paternoster et al, 1983), but it departs from some research on student misconduct (Michaels and Miethe, 1989;Salem and Bowers, 1970;Tittle and Rowe, 1973). Tittle and Rowe (1973) implemented moral appeals and the threat of a sanction when giving students the opportunity to cheat and determined that the moral appeal had no effect but the sanction threat reduced student cheating.…”
Section: Discussionsupporting
confidence: 57%
“…The existence of honor codes at universities is linked to less student cheating (McCabe and Trevino, 1993;Salem and Bowers, 1970). Honor codes may influence cheating because of the messages they send and because they enhance legitimacy.…”
Section: Legitimacy and Academic Misconductmentioning
confidence: 99%
“…Rodgers and Bullock (1976a: 165) find that strong enforcement is the major explanation of school desegregation in 31 Georgia school districts. The public law literature generally finds that the probability of being sanctioned is more important than the size of the penalty in exacting compliance (Tittle and Rowe, 1974;Salem and Bowers, 1972;Logan, 1975;Erickson and Gibbs, 1975).…”
Section: Environmentmentioning
confidence: 99%